Student’s Algebraic Thinking Ability in Solving Mathematical Problems Based Misconceptions - Anggriati Ledu Ngaba; Nuriana Rachmani Dewi; St. Budi Waluya (Journal of Educational Sciences, 2023)
Mastering algebraic concepts and skills has been one of the demands in the Indonesian curriculum for the past few decades. Teaching algebraic concepts and skills is one of the materials taught from the junior high school to university level. Therefore, it is mandatory for pre service mathematics teacher students to master and even fluently use algebraic concepts in order to develop students' algebraic thinking skills. Thus, this study aims to understand and obtain a description of students' algebraic thinking abilities and misconceptions in solving problems. This research using descriptive qualitative. Analysis was conducted using tests and in-depth interviews with students who had taken linear algebra courses in semester 3 of the Mathematics Education Study Program at private university in NTT. Student’s algebraic thinking skills in solving problems were analyzed using Kieran's (2004) indicators consisting of: generational activities, transformational activities, and global meta-level activities. The results of the research show that…. In generational activities, students in the low, medium, and high categories have misconceptions. In transformational activities and global meta-level activities, misconceptions are only carried out by low category students.